Factors affecting the ripening and flavor of bagoong alamang (shrimp paste), (Acetes sp.) - Nieto, Marceliano B.
The processing of bagoong alamang, a salt-ripened shrimp paste prepared from Acetes shrimp was studied in order to obtain practical indications regarding optimum salt-top-shrimp ratio, time of delay prior to salting and length of ripening. Chemical indices including α-amino N, volatile N, volatile acids and pH were monitored during fermentation as well as the sensory qualities of the product. Relevant tests such as microaerophilic count, moisture content, salt content, aw and astaxanthin measurements were also undertaken. The results obtained indicated the following: Effect of Salt-to-Shrimp Ratio. The aroma and taste developed better in the less salty samples, i.e. in the 1:6 and 1:7 ratios but the 1:6 was chosen optimum. The product had a salt content of 13.2% and aw of 0.86. Ripening was hindered with increasing salt and the 9-day period was not enough when 1:3, 1:4 and even 1:5 ratios were used. Volatile acid contents were generally the same in all smples but the amino N and volatile N were inversely affected by salt content. The atypical smell present in the fresh alamang disappeared faster with decreasing salt and vice versa. Effect of time of Delay Prior to Salting. The delay of 7 hours after catch at ambient temperatures (28 ± 2°C) gave the best product in terms of aroma and taste. This was characterized by volatile acid content of 2.86 mg/g, amino N of 10.58 mg/g, volatile N of 1.78 mg/g and pH of 6.7 after 9 days of fermentation. The volatile acids was found responsible for the cheesy smell. Using fresh alamang, aroma was very weak because of low volatile acid content. Using longer delays, off-smell of ammonia and sulfides become more and more pronounced. The volatile acids formed at a rate of around 0.5 mg/hour in the raw, unsalted alamang but was very much hindered upon the addition of salt and occured at a rate of 0.03 mg/day in the sample salted with 1:6 ratio. The rates of increase of the amino N and volatile N were affected by the initial concentrations as a result of salting delay. A pinkish color formed when 2-to-3-hour old alamang were used and reddish purple characterized by the Munsell notation 10 RP 5/4 and 10 RP 6/3 when delay was 5 hours or more. Effect of Ripening Time. Using the 1:6 salt-to-shrimp ratio and delay of 7 hours at ambient, a ripening period of 5-7 days at room temperature (31 ± 2°C) was found optimum for the development of aroma and taste. Volatile acid content was around 2.70 mg/g, volatile N ranged from 1.72 to 2.40 mg/g, α-amino N was around 10.00 mg/g and pH was between 6.5 to 6.7. The bulk of the volatile acids was pre-formed. The cheesy aroma, however, appeared only after a day of ripening simultaneous with the drop of pH to the acid side. Mainly acetic acid comprised the volatile acids found. The formation of amino N and volatile N levelled off towards the end of the 9-day ripening period implying feedback inhibition. The bacterial counts were composed mainly of the original flora surviving in the product and not those growing. There was an enormous gas production during the first 4 days of ripening. The reddish purple color formed already on mixing and did not changed markedly anymore. Consumer evaluation of the standardized product against market samples revealed very high preference for the former in terms of aroma. The natural color of the bagoong alamang was also highly acceptable.